Nourishing futures: The Philippines promote native foods in school meals - Mendonce, Sharon; Borelli, Teresa; Honeycutt, Sydney; Anunciado, Ma. Shiela; Umali, Diana Jean (School Meals Coalition, 2024)
Imagine a bustling schoolyard in the Philippines, where children eagerly tend to their vibrant classroom garden. As part of a school gardening programme, the students are excited to harvest the fruits and vegetables they have carefully cultivated. In just a few hours, these nutritious foods will be served on their lunch plates. This heartwarming scene reflects broader efforts across the Philippines to integrate traditional and indigenous fruit and vegetables into school meals and promote healthy eating habits. Driven by a commitment to improve the quality of school meals, the Philippines, as a School Meals Coalition member, has introduced various initiatives aimed at supporting the health and well-being of students. Beyond combatting hunger, these efforts are designed to enhance learning outcomes and foster a brighter, healthier future for the nation.